In vitro control of curvularia leaf spot and basal stem rot diseases on oil palm using crude weed extracts / Norsyazwina Mohamed Rosli - Mohamed Rosli, Norsyazwina (Faculty of Plantation and Agrotechnology, 2018)
Malaysia currently involves in exporting the palm oil and generates profits from it. Apart from the massive extension of oil palm plantation sectors in Malaysia, Malaysian must play the important roles to protect the plant from infected with diseases. The widespread of the Basal Stem Rot (BSR) and Curvularia leaf spot have become the major treat towards the oil palm plantation because there were no effective biocontrol methods for both diseases and currently depend on chemical usage. Therefore, the main objectives of this study were to determine the in vitro antifungal activities of weed extracts to suppress the mycelial growth of fungi Ganoderma sp. causing BSR and Curvularia sp. caused Curvularia leaf spot on oil palm using food poisoning technique and to compare the in vitro antifungal activities between crude weed extracts used in this study for management of BSR and Curvularia leaf spot diseases on oil palm. In vitro studies, we have found the most effective crude weed extract amongst ten species tested which was identified as Solanum torvum for Curvularia sp. with 63.89% of mycelial growth inhibition while for Ganoderma sp. with 76.10% of mycelial growth inhibition. Apart from that, we also identified the common weed species that can be used as biocontrol agents for both fungi of Curvularia sp. and Ganoderma sp. which where Solanum torvum and Chromolaena odorata weed species.